(untitled) (Research, Society and Development, 2021)
Understanding the different concepts of learning, such as the relationship between teaching and learning, is of utmost importance for education since learning is discussed by different educational theorists. That said, the teaching and learning process is related to the interaction between teachers and students in the educational context, and during this process situations may emerge that can affect teaching as well as learning. Thus, this research aims to identify the elements that may interfere in the teaching and learning process, presenting the internal and external factors that contribute to such interference. The research is classified as basic in nature, with a quanti-qualitative methodological approach, and its objectives are bibliographic and exploratory. A survey was carried out in the CAPES and Google Academic databases, aiming to subsidize the following questions: which factors may interfere in the teaching and learning process? What are the influences of these factors in the school space? At the end of the research, it was possible to identify that some of the factors that cause damage to learning may be related to emotional, social, and family issues.